Virulent properties of pectobacteria isolated from plant samples on the territory of Belarus - Chengyue, Shao; Evtushenkov, Anatoli N. (Experimental Biology and Biotechnology, 2023)
The phytopathogenic bacteria Pectobacterium carotovorum, P. parmentieri and P. brasiliense isolated from plants on the territory of Belarus differed in their ability to infect potato, carrot, onion and Chinese cabbage tissues with artificial infection. Strains of species P. carotovorum and P. brasiliense turned out to be highly virulent. Bacteria P. parmentieri were characterised by low virulence, which was manifested in the low efficiency of infection of onion, carrot, Chinese cabbage plants and reduced macerating and pectate lyase activities.